Ag(e)ing and Degradation of Supercapacitors: Causes, Mechanisms, Models and Countermeasures - Chen, Xuecheng; Wu, Yuping; Holze, Rudolf (Molecules (Basel, Switzerland), 2023)
The most prominent and highly visible advantage attributed to supercapacitors of any type and application, beyond their most notable feature of high current capability, is their high stability in terms of lifetime, number of possible charge/discharge cycles or other stability-related properties. Unfortunately, actual devices show more or less pronounced deterioration of performance parameters during time and use. Causes for this in the material and component levels, as well as on the device level, have only been addressed and discussed infrequently in published reports. The present review attempts a complete coverage on these levels; it adds in modelling approaches and provides suggestions for slowing down ag(e)ing and degradation.